Лингвостилистический анализ сравнений в повести Н. Гоголя "Ночь перед Рождеством" - Банзерук, О. В. (Видавництво НДУ ім.М. В. Гоголя, 2017)
У статті на матеріалі гоголівської повісті подано лінгвостиліс-тичний аналіз порівняння. Розглянуто структуру і граматичні типи компаративів. Виділено й охарактеризовано функціонально-стиліс-тичні моделі, пов’язані з характеристиками образів персонажів.
Comparison is two-sided phenomenon because it is the reception of logic, the operation of mentality and special linguistic and artistic means called trope simultaneously. Following the other researchers we consider the phenomenon of comparison as comparison of one subject, fact or concept with another on the basis of a certain feature. The analysis of comparative models in the story "The night before Christmas" written by Gogol promotes the disclosure of ideological content and detection of specific methods of using these author`s favourite bright means. While analyzing the story that was mentioned we distinguished and characterized several functional-stylistic models of Gogol`s comparisons.
Keywords: порівняння; компаратив; структура; грама-тичні типи компаративів